Fundamentals of technical writing - Nem Singh, Rosario P.; Calixihan, Jovita O. (Mandaluyong City : National Book Store, 1994)
This books attempts to answer the need to learn how to present scientific and technical information, a national resource necessary for socio-economic development.
1. Introduction -- 2. Characteristics of technical writing -- 3. Mechanics of style -- 4. Planning -- 5. Methods of organizing material (A) -- 6. Methods of organizing material (B) -- 7. Methods of organizing material (C) -- 8. Analysis and interpretation -- 9. Beginnings and endings -- 10. The scientific attitude -- 11. Science news reporting -- 12. Recommendation reports -- 13. Progress report -- 14. Proposals -- 15. Library research and report -- 16. Writing business letters -- 17. Graphic aids.
Includes bibliographical references.
Keywords: TECHNICAL WRITING